Response to cimetidine in a 1-year-old child with PFAPA syndrome - Taniguchi, Kazuto; Ono, Nobuyasu; Sakai, Tatsuya; Ichiyama, Yasunobu; Uemichi, Kazuyasu (The Turkish Journal of Pediatrics, 2016)
Periodic fever, aphthous stomatitis, pharyngitis, and cervical adenitis (PFAPA) syndrome is characterized by periodic febrile attacks recurring regularly every 2 to 8 weeks. Although tonsillectomy is offered as an effective treatment, the effectiveness of cimetidine treatment is still controversial. In this article, we describe two cases. A 1-year-old girl with PFAPA syndrome received cimetidine treatment and febrile attacks were reduced. Tonsillectomy was successfully performed on a 6-year-old boy with PFAPA syndrome. We suggest that the use of cimetidine may reduce febrile attacks of PFAPA syndrome until an age that is safer for tonsillectomy.
Keywords: PFAPA syndrome; cimetidine; febrile attacks; tonsillectomy